Degradation of PEIE interlayer in PTB7:[70]PCBM based solar cells characterized by impedance spectroscopy. (1st March 2017) - del Pozo, Gonzalo; Arredondo, Belén; Romero, Beatriz; Susanna, Gianpaolo; Brunetti, Francesca
Graphical abstract: Highlights: Degradation of PTB7:[70]PCBM OSC with PEIE layer has been studied by means of IS. Flat band potential evolution indicates a degradation of cathode work-function. Change in resistance and capacitance of PEIE layer that worsen the performance. Decrease of carrier mobility. Abstract: In this work PTB7:[70]PCBM (Poly[[4, 8-bis[(2-ethylhexyl)oxy]benzo[1, 2-b:4, 5-b′]dithiophene-2, 6-diyl] [3-fluoro-2-[(2-ethylhexyl)carbonyl] thieno[3, 4-b] thiophenediyl]]:[6, 6]-Phenyl-C71-butyric acid methyl-ester ([70])) based solar cells with PEIE (Polyethylenimine, 80% Ethoxylated) as electron transport layer (ETL) have been characterized along two months using impedance spectroscopy (IS). The experimental data were fitted using an electrical circuit and the time evolution of circuital parameters was analyzed. At high voltages, the capacitance associated to the PEIE layer decreases within the first days of measurements while the resistance increases during the same period. The flat band voltage, Vfb, obtained from a Mott-Schottky analysis, decreases with measuring time around 0.1 V, suggesting a deterioration of PEIE interface that no longer improves the ITO work-function. Carrier mobility decreases from 2.2 × 10 −3  cm 2 /Vs to 2.4 × 10 −4  cm 2 /Vs within the first few days of measurements.